Protecting and rejuvenating ageing skin by regulating endogenous hyaluronan metabolism using adipose-derived stem cell-secreted siRNAs - Sun, Benben; He, Yanqiu; Zhang, Lingzhu; Liu, Siyu; Chen, Menghan; Pan, Jinmeng; Fang, Jingwen; Wang, Ye; Jiang, Haiyue; Liu, Xia; Zhang, Chen-Yu; Li, Jing (Frontiers in Medicine, 2025)
BackgroundLoss of moisture is the primary cause of skin ageing and dysfunction. The skin’s hydration largely depends on hyaluronan (HA) and its ability to retain water. Ultraviolet (UV) irradiation, which accounts for 80% of skin ageing (commonly referred to as photoaging), gradually disrupts the balance of HA metabolism, leading to a reduction in HA levels, dehydration, and, ultimately, the formation of wrinkles.MethodsIn this study, we develop an RNAi-based strategy to treat aged skin by modulating endogenous HA metabolism. Hyaluronidase 2 (HYAL2), an enzyme responsible for HA degradation, is selected as the therapeutic target, given its significant upregulation in photoaged skin. To deliver the siRNA targeting HYAL2 to the skin, human adipose-derived stem cells (ADSCs) are engineered to stably express and secrete HYAL2-targeting siRNAs (ADSC/siRH) via small extracellular vesicles (sEVs).ResultsIn vitro experiments demonstrate that ADSC-delivered siRNAs are successfully internalised by recipient cells, where they restore UV-induced HA reduction by inhibiting HYAL2 expression. In vivo experiments revealed that subcutaneous implantation of engineered ADSCs prior to UV exposure significantly protects mouse skin from accelerated HA degradation, helping to retain water content and prevent UV-induced dryness. Furthermore, the application of engineered ADSCs to aged mouse skin can markedly restore HA and water content, effectively smoothing deep wrinkles and improving skin appearance.ConclusionWe developed an effective biological strategy to combat skin ageing and damage by preserving endogenous HA levels, which could be applied for facial rejuvenation in the future.